(3LhGgQ GdSeGW aj PcQ efGbH GdTQja GdQaGYj SjOj YHOGddg GdNjGWs ((3GdeOfj GHf GdMGL eMeO GdHQcI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CLJHj ChdjGAg hCOdi dcd efge OdGAg s
(3BNQgG (B:s
(3Yf TjN GdeTGjN CHj GdYHGS SjOj CMeO GdTgjQ HQRhb QVi Gddg Yfge hfaYfG Hge Bejf hGdMeO ddg QH GdYGdejf s
(3YQa ajg GdeDda HGdTjN GHf eMeO YHOGddg GdNjGW GdMSjfj GdQaGYj GdRQghfj GdeJhaj SfI (B939(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B144 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B196 s
Keywords: (3GdJGQjNs